Cercas da reforma agrária: sonhos, conflitos e contradições assentamento Rio Das Pedras / Uberlândia - MG - Oliveira, Elisângela Magela (2007)
The present research studies the historical trajectory of the nesting River of the Rocks, located in the city of Uberlândia, Minas Gerais of State. The central objective of the work consists of studying the social direction and politician of the agrarian reform in Uberlândia, searching to understand the reasons for which that nesting, as many that occur in the country, did not represent advances in the way of the maintenance of the workers in the conquered land. Made up of 87 families, the nesting River of the Rocks had its officialization legalized in October of 1997, moment where the Alçada Court, in Belo Horizonte, suspended the Action of repossession effected against the movement, effected by Josias de Freitas, proprietor of the farm, allowing the permanence of the families in the place. Passed the period of encampment, the workers had continued in a situation of difficulties. With the scarcity of resources and the little knowledge on culture of the land, the majority of the workers if sees in the difficult condition of inexperienced peasants, facts that had lead to the questioning in the way as the agrarian reform is being lead in the country. For in such a way, the study it counted on a specific bibliography and different sources of research on the agrarian question in Brazil. Texts proceeding from the National Institute of Settling and the Reformation Agrarian-NISRA had been used, of the Brazilian Institute of Geography and Statistics-BIGS, of the Pastoral Commission of the Land-PCL, the Municipal City hall of Uberlândia and the Land, Work and Freedom Movement -LWFM, entity that the occupation of the farm organized River of the Rocks, together to the workers without land; beyond periodicals and reviewed. Estimated the theoretician-methodology had left of diverse references, if not concentrated in specific theories.